2021
DOI: 10.1029/2020gl090913
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of the Intraseasonal SST Variability by the Diurnal Cycle of SST Revealed by the Global Tropical Moored Buoy Array

Abstract: The diurnal cycle of sea surface temperature (SST), which is driven by the diurnal variation of solar radiation, is a fundamental oscillation in the ocean (Soloviev & Lukas, 2006). The amplitude of the diurnal cycle of SST (dSST) is primarily determined by surface solar radiation and surface wind speed (Gentemann et al., 2003; Kawai & Wada, 2007; Price et al., 1986; Webster et al., 1996). Stronger solar radiation introduces more heat to the ocean inducing a larger dSST, while stronger wind forcing drives stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…The fSST is the SST free of diurnal variability, which is usually defined as the night-time minimum or the predawn value at depths of 1-5 m (Donlon and The GHRSST-PP Science Team, 2005). In this study, we used the night-time minimum as the definition for fSST following Yan et al (2021). Phase composites of the calculated SH and LH at two buoy sites (8 N, 137 E) (B8137) and (0 N, 156 E) (B0156) based on the abovementioned SSTs are given in Figure 11.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fSST is the SST free of diurnal variability, which is usually defined as the night-time minimum or the predawn value at depths of 1-5 m (Donlon and The GHRSST-PP Science Team, 2005). In this study, we used the night-time minimum as the definition for fSST following Yan et al (2021). Phase composites of the calculated SH and LH at two buoy sites (8 N, 137 E) (B8137) and (0 N, 156 E) (B0156) based on the abovementioned SSTs are given in Figure 11.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, using a high-vertical-resolution OGCM, Bernie et al (2007) concluded that including the effects of dSST increases the SST-ISV by approximately 20% across the equatorial Indo-Pacific Ocean. Yan et al (2021) quantified the effect of the dSST on ISV based on the global tropical moored buoy array. They found that the intraseasonal SST variability is indeed amplified by the dSST in most of the tropical oceans, especially in the Indo-Pacific warm pool, but weakened in the equatorial cold tongues of the Pacific and Atlantic Oceans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that the diurnal variability of surface and subsurface ocean impacts diurnal atmospheric properties and can modulate the intraseasonal and seasonal ocean and atmospheric processes. Observational studies (Mujumdar et al, 2011;Yan et al, 2021) have shown rectification of intraseasonal SST by diurnal variations of SST over most tropical oceans. Through coupled model experiments, Bernie et al (2007Bernie et al ( , 2008 have shown that the rectification of daily-mean SST by the diurnal variability of SST can increase the long-term-mean SST by 0.2 • -0.3 • C and an improvement in the mean precipitation simulated by the model.…”
Section: Diurnal Precipitationmentioning
confidence: 99%
“…The cumulative effect of diurnal warm layer and cooling can result in intra-daily variability of ocean skin temperature. Observational and modeling studies (Fairall et al, 1996b;Slingo et al, 2003;Shinoda, 2005;Bernie et al, 2007Bernie et al, , 2008Woolnough et al, 2007;Mujumdar et al, 2011;Yan et al, 2021) have reported possible impacts of diurnal skin temperature variability on daily, intra-seasonal, and seasonal mean and variability by modulating ocean-atmospheric parameters such as SST, mixed layer depth, air pressure, humidity, low-level cloud, and convection.…”
Section: Introductionmentioning
confidence: 99%